Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem - Fioretto, Antonietta; Di Nardo, Carmelina; Papa, Stefania; Fuggi, Amodio (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).
Keywords: Cellulose; cistus incanus; decomposition dynamics; Lignin; myrtus communis; nitrogen; Quercus ilex

Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem - Fioretto, Antonietta; Di Nardo, Carmelina; Papa, Stefania; Fuggi, Amodio (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).
Keywords: Cellulose; cistus incanus; decomposition dynamics; Lignin; myrtus communis; nitrogen; Quercus ilex